Effect of Ethanol Solvents in the Extraction Process of Bioactive Compounds from Brown Seaweed (Sargassum sp.) with the Ultrasound Assisted Extraction Method - Slamet Pujianto; Boy Arief Fachri; Istiqomah Rahmawati; Erna Subroto (Program Studi Teknik Kimia Universitas Jember, 2022)
Sargassum sp., part of brown algae, is traditionally used as animal feed. Nonetheless, Sargassum contains phenolic compounds that promise to be the raw material of natural antioxidants. The work is to extract phenolic compounds from Sargassum sp. in ethanol and to investigate the effect of the process on phenol yields. Several dried Sargassum sp. are milled in a certain size and extraction using ultrasound assisted extraction with ethanol solvent. Process variables are the extraction time (30-50 minutes) and the Ratio of Sargassum sp. to ethanol which is 5:100-15:100 (b/v), and power of 170-190 watts. Phenol compounds are quantified using the error acid method. The DPPH method is performed to check the antioxidant activity. To investigate the influence of the process, surface response methods based on central composite designs are applied in this work. 153.334 mgGAE/g in 30-minute extraction conditions, 170 watts of power, and a ratio between masses and solvents of 0.05. The antioxidant activity (IC50) of Sargassum sp. extract is 87.57 ppm.